The Intersection of Judicial Attitudes and Litigant Selection Theories: Explaining U.S. Supreme Court Decision-Making - Jeff Yates; Elizabeth Coggins (Washington University Journal of Law & Policy, 2009)
This Essay tests an integrated model of decision-making on case outcomes in the United States Supreme Court and employs an interactive specification to assess the influence of judicial ideology on Supreme Court outcomes, simultaneously accounting for litigants’ and justices’ case selection (sorting) behavior.
Keywords: Judicial process; Judicial discretion; Judicial decision-making; Theories of decision-making; U.S. Supreme Court